Identification and characterization of virulence factor of several Indonesian Xanthomonas oryzae pv. oryzae - FATIMAH FATIMAH; APON ZAENAL MUSTOPA; IQBAL KUSNANDARSYAH (Indonesian Society for microbiology, 2014)
Xanthomonas oryzae pv. oryzae (Xoo) is the bacterial causative agent of leaf blight in rice (Oryza sativa L.), the most serious bacterial disease of rice in many rice growing areas worldwide. This study aimed to identify and characterize several virulence factors of seven Xoo isolates from Yogyakarta, West Java, and West Sumatera. The identification of Xoo using 16S rRNA confirmed high homology to Xanthomonas oryzae pv. oryzae PXO99A and revealed three groups. The first group was Xoo93229, the second group containing Xoo1110, Xoo1122, Xoo1130, Xoo7624 and Xoo8024 as the same cluster with PXO99A and the third group was KACC10331 and MAFF311018. The amounts of exopolysaccharide (EPS) and cellulase produced were varying depending on the Xoo isolates. The EPS were produced more by isolate Xoo1130, Xoo1122 and Xoo8024. All tested isolates revealed similar cellulase activity except for isolate Xoo8024. The pathogenicity assay among the Xoo isolate showed that all tested isolates were virulent except Xoo7624. The in planta assay revealed that the tested isolates have multiplied and continued increasing the population size except for Xoo1110 and Xoo7624. High yield of EPS, cellulase activity, more virulence, and increasing population size revealed from isolate Xoo1130 and Xoo1122.